Optimizing conditions for labeling of mesenchymal stromal cells (MSCs) with gold nanoparticles: a prerequisite for in vivo tracking of MSCs - Nold, Philipp; Jungebluth, Philipp (Journal of nanobiotechnology, 2017)
Mesenchymal stromal cells (MSCs) have an inherent migratory capacity towards tumor tissue in vivo. With the future objective to quantify the tumor homing efficacy of MSCs, as first step in this direction we investigated the use of inorganic nanoparticles (NPs), in particular ca. 4 nm-sized Au NPs, for MSC labeling. Time dependent uptake efficiencies of NPs at different exposure concentrations and times were determined via inductively coupled plasma mass spectrometry (ICP-MS).